Cross-Border E-Commerce: Growth, Challenges, and Strategies - Nandeshwar, Dilip Mukunda (AG Volumes, 2024)
Global trade continues to develop because cross-border e-commerce, a new driver for the expansion of international trade, opens up new markets and possibilities. The development of logistics has been influenced by trade; however, the excellent growth of cross-border e-commerce is inextricably linked to the establishment of intelligent and efficient logistics services. In this article review the various literature’s study on growth, challenges and strategies interact in “Cross-Border E-Commerce”. It concluded that the growth of CBEC is transforming global trade ecosystems, yet it faces limitations in dataset sharing and platform scalability. A comprehensive system design can enhance consumer conversion, optimize resource integration, and improve platform efficiency. Strategically, collaboration between e-commerce and logistics enterprises, leveraging cloud computing and big data, fosters an intelligent logistics system and standardized service management. However, CBEC faces challenges such as inefficient customs clearance, high logistics costs, security concerns, and talent shortages. Addressing these barriers with innovative strategies and digital marketing advancements can drive sustainable growth and international market success.